Optimization of Phage-Based Pathogen Detection During Sample Shipment - Cheing G., Roberto S. (Zamorano: Escuela Agrícola Panamericana, 2020., 2020)
Foodborne illnesses are diseases caused by pathogen microorganisms present in the food matrix. Various organizations regulate the laws and guidelines that must be followed to avoid contamination of food with pathogen microorganisms. The presence of pathogen microorganisms is sufficient cause to deny the entry of food shipments. That is the reason that rapid detection of pathogen microorganisms is of vital importance. In this study, a bioluminescence detection method for Escherichia coli O157:H7 was evaluated. For this the ΦV10 Lux + Kanamycin resistance was used. A Randomized Complete Block Design (RCB) was used to measure the effect of seven concentrations of E. coli O157:H7, seven concentrations of ΦV10 Lux + Kanamycin resistance, two incubation temperatures, and five enrichment times before the addition of kanamycin. The data were analyzed using a Chi-square test. The sensitivity, specificity, accuracy, positive and negative predictive values of the method were also calculated, obtaining 95, 100, 96, 100 and 36%, respectively. There was no difference in the bioluminescence detection when using bacteria concentrations from 5 Log CFU/mL to 7 Log CFU/mL; phage concentrations from 7 Log PFU/mL to 8 Log PFU/mL (P = 0.9432); 1, 2, 3, 4 or 5 hours enrichment time before adding kanamycin (P = 0.9889) or incubation temperatures of 21 or 37 ˚C (P = 0.9364).